2020
DOI: 10.1093/infdis/jiaa479
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2–Specific Antibody Detection for Seroepidemiology: A Multiplex Analysis Approach Accounting for Accurate Seroprevalence

Abstract: Background The COVID-19 pandemic necessitates a better understanding of the kinetics of antibody production induced by infection with SARS-CoV-2. We aimed to develop a high throughput multiplex assay to detect antibodies to SARS-CoV-2 to assess immunity to the virus in the general population. Methods Spike protein subunits S1 and RBD, and Nucleoprotein were coupled to distinct microspheres. Sera collected before the emergence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 23 publications
3
130
0
Order By: Relevance
“…Ng and colleagues identified such cross-reacting antibodies against non-RBD S-protein epitopes in sera originating from the pre-pandemic era, which also demonstrated activity in the neutralization assay [44]. Cross-reacting antibodies due to endemic common cold coronavirus disease have also been demonstrated by others [45][46][47][48][49]. It remains to be seen whether an immune-reactivity to non-S1-RBD spike protein lowers the risk of contracting COVID-19 during the pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…Ng and colleagues identified such cross-reacting antibodies against non-RBD S-protein epitopes in sera originating from the pre-pandemic era, which also demonstrated activity in the neutralization assay [44]. Cross-reacting antibodies due to endemic common cold coronavirus disease have also been demonstrated by others [45][46][47][48][49]. It remains to be seen whether an immune-reactivity to non-S1-RBD spike protein lowers the risk of contracting COVID-19 during the pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…The aim of this study was to assess the clinical performance of a multiplex assay designed to detect S1-, S2-, N-, RBD- and NTD-directed antibodies. The major promises of multiplex methods for anti-SARS-CoV-2 antibodies included increased performance in terms of sensitivity and of specificity [ 25 , 26 , 27 , 28 ], which is in line with the orthogonal testing algorithm proposed by the Centers for Disease Control and Prevention (CDC). The simultaneous detection of several antigens could also permit to predict the disease outcome by identifying various antibody signatures and allow to assess the immunological response to future vaccines with more objectivity [ 29 ].…”
Section: Introductionmentioning
confidence: 96%
“…Testing for antibodies specific to different viral antigens appeared to us a practical approach to increase confidence of the immune response assessment. It was recently shown that a multiple-antigen approach can indeed increase specificity of testing [ 13 ]. The focus of this study was to develop an accurate, robust, and reproducible multi-antigen testing approach which would allow for maximum specificity in the ELISA format, while maintaining an adequate sensitivity level.…”
Section: Introductionmentioning
confidence: 99%
“…In other approaches involving negative and positive training sample sets, statistical methods, such as the Youden J statistic cutoff, are used to determine absolute antibody threshold concentrations, and in following experiments absolute concentration values of studied samples to said threshold are calculated and compared [ 13 ]. However, this also may not be convenient during large-scale analysis, e.g., population screening, where the robustness of the system is crucial and the qualitative tests may show significant bias when switching between laboratories, equipment, and operators.…”
Section: Introductionmentioning
confidence: 99%